doGlycans-Tools for Preparing Carbohydrate Structures for Atomistic Simulations of Glycoproteins, Glycolipids, and Carbohydrate Polymers for GROMACS - Danne, Reinis; Poojari, Chetan; Martinez-Seara, Hector; Rissanen, Sami; Lolicato, Fabio; Róg, Tomasz; Vattulainen, Ilpo (Journal of chemical information and modeling, 2017)
Carbohydrates constitute a structurally and functionally diverse group of biological molecules and macromolecules. In cells they are involved in, e.g., energy storage, signaling, and cell-cell recognition. All of these phenomena take place in atomistic scales, thus atomistic simulation would be the method of choice to explore how carbohydrates function. However, the progress in the field is limited by the lack of appropriate tools for preparing carbohydrate structures and related topology files for the simulation models. Here we present tools that fill this gap. Applications where the tools discussed in this paper are particularly useful include, among others, the preparation of structures for glycolipids, nanocellulose, and glycans linked to glycoproteins. The molecular structures and simulation files generated by the tools are compatible with GROMACS.
Keywords: glykolipidy; glykoproteiny; Glycolipids; Molecular Dynamics Simulation; Software; polysacharidy; software; sacharidy; biochemie sacharidů; simulace molekulární dynamiky; Glycoproteins; Polysaccharides; Carbohydrates; Carbohydrate Biochemistry